Applying psychology to du' at resource management : potentials and limitations - Alias, Alizi (2010)
The objective of this paper is to discuss the potentials and limitations of applying Industrial and Organisational Psychology to improve Du`at (Islamic callers) Resource Management. This is a conceptual paper on how the principles and theories in Industrial and Organisational Psychology can be applied to da`wah and management based on reviews from advanced level sources in Industrial and Organisational Psychology. First, the paper will provide an overview on the concept of Industrial and Organisational Psychology and its several sub-topics. The sub-topics are: (1) job analysis, (2) personnel selection, (3) performance appraisal, and (4) training. Next, the paper will discuss some the sub-topics in terms of Islamic redefinition and their potentials and limitations in improving du`at resource management and da`wah organisational behaviour. Finally, the paper ends with suggestions for da`wah researchers and da`wah organisations.